2022
DOI: 10.3390/met12060951
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Control on Properties and Residual Stresses of Additive-Welded High-Strength Steel Components

Abstract: Advanced high-performance filler metals for wire arc additive manufacturing (WAAM) exist on the market already. Nevertheless, these high-strength steels are not yet widely used in industrial applications due to limited knowledge of cold-cracking susceptibility, welding residual stresses, and therefore sufficient safety in terms of manufacturing and operation. High residual stresses promote cold-cracking risk, especially in the welding of high-strength steels, as the result of a complex interaction between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…This adjustment is made by controlling the values of wire feeding rates and travel speed (TS). With higher heat input the lower RS is observed on the surface of the top layer by long-time cooling durations [67]. Welding RS was measured using five experimental methods: X-ray diffraction (XRD), neutron diffraction (ND), incremental deep hole drilling (iDHD), incremental center hole drilling (iCHD), and contour method (CM) [68].…”
Section: Residual Stress In Waamed Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…This adjustment is made by controlling the values of wire feeding rates and travel speed (TS). With higher heat input the lower RS is observed on the surface of the top layer by long-time cooling durations [67]. Welding RS was measured using five experimental methods: X-ray diffraction (XRD), neutron diffraction (ND), incremental deep hole drilling (iDHD), incremental center hole drilling (iCHD), and contour method (CM) [68].…”
Section: Residual Stress In Waamed Productsmentioning
confidence: 99%
“…As researchers delve deeper into WAAM, they have discovered significant enhancements inside the grain arrangement and material properties of the produced components [69]. The transformation of large, elongated grains into smaller, uniformly shaped grains in both the inner and intermediate layers is accomplished by adjusting the amount of heat applied [66,67]. The influence of heat input on the RS, macroscopic structure, microscopic composition, and mechanical characteristics of the components fabricated through the WAAM procedure is studied in [70,71]…”
Section: Residual Stress In Waamed Productsmentioning
confidence: 99%
“…For AM, the path coordinates are essentially derived from a CAD model using slicers and interpreted into Fig. 1 Block diagram for the signal and material flow of the robot-based WAAM welding system; welding parameters (welding speed v T , volume flow per time V/t), which determine the layer width b S and height h S [23] executable welding programs. The robot controller interprets the programmed lines and controls the traversing movement and the welding machine.…”
Section: Waam Welding Systemmentioning
confidence: 99%
“…Fig. 2 a Welding parameters and build-up strategy for a 9 mm thick wall for WAAM experiments, b specification of the reference geometry (open hollow cuboid); CAD model and weld result, c welding parameters[23] …”
mentioning
confidence: 99%
“…Interestingly, the distortion is much more significant when the number of layers is small [16]. The geometry of the built component also affects the residual stress; for instance, the corner of the rectangle shows extremely high residual stress [17]. The adaptive heat flow to the substrate or the workpiece is one of the latest approaches to controlling residual stress and distortion; for instance, Doumenc et al [18] used a cooling system to keep the substrate at 20 • C such that after every layer deposition, 20 • C is reached in 40 s. Differently, Fan et al [19] suggested trailing cooling of argon gas to −15 • C, followed by depositing a subsequent layer, which reduced residual stress.…”
Section: Introductionmentioning
confidence: 99%